The Leadership Role of Tuan Teachers in Developing Islamic Boarding Schools in Lombok - Badrun Badrun (STAI Hubbulwathan Duri, 2023)
The leadership of teachers in Islamic boarding schools is something that is important to do in order to become a quality Islamic boarding school. This research aims to reveal and elaborate three things, namely: the concept of master teacher leadership in developing Islamic boarding schools, strategies in developing Islamic boarding schools and the benefits that Islamic boarding schools and the surrounding community gain from developing Islamic boarding schools. The results of data analysis show that the teacher's concept in developing Islamic boarding schools is collective-collegial, democratic-participatory and consultative-authoritative. Meanwhile, the strategy carried out by the teacher is to build and maintain trust, empowerment, synergy, innovation, flexible policies and forming solid cooperation. The benefits from the results of Islamic boarding school development are felt and enjoyed by various parties, namely: first, the availability of basic necessities for students, alumni, guardians of students, Islamic boarding school institutions and the surrounding community. Second, the opening of new job opportunities for the community, especially residents around the Islamic boarding school. Third, Islamic boarding schools have economic independence so they have authority and independence in regulating and managing Islamic boarding school institutions. The research has implications for the development of Islamic boarding schools in the field of entrepreneurship based on religious values